Waiting to win: elevated striatal and orbitofrontal cortical activity during reward anticipation in euthymic bipolar disorder adults - Robin Nusslock; Jorge Almeida; Erika E. Forbes; Amelia Versace; Ellen Frank; Edmund J LaBarbara; Colin Klein; Mary L. Phillips (2012)
Nusslock R, Almeida JRC, Forbes EE, Versace A, Frank E, LaBarbara EJ, Klein CR, Phillips ML. Waiting to win: elevated striatal and orbitofrontal cortical activity during reward anticipation in euthymic bipolar disorder adults. Bipolar Disord 2012: 14: 249–260. © 2012 The Authors. Journal compilation © 2012 John Wiley & Sons A/S. Objective: Bipolar disorder may be characterized by a hypersensitivity to reward‐relevant stimuli, potentially underlying the emotional lability and dysregulation that characterizes the illness. In parallel, research highlights the predominant role of striatal and orbitofrontal cortical (OFC) regions in reward‐processing and approach‐related affect. We aimed to examine whether bipolar disorder, relative to healthy, participants displayed elevated activity in these regions during reward processing. Methods: Twenty‐one euthymic bipolar I disorder and 20 healthy control participants with no lifetime history of psychiatric disorder underwent functional magnetic resonance imaging (fMRI) scanning during a card‐guessing paradigm designed to examine reward‐related brain function to anticipation and receipt of monetary reward and loss. Data were collected using a 3T Siemens Trio scanner. Results: Region‐of‐interest analyses revealed that bipolar disorder participants displayed greater ventral striatal and right‐sided orbitofrontal [Brodmann area (BA) 11] activity during anticipation, but not outcome, of monetary reward relative to healthy controls (p < 0.05, corrected). Whole‐brain analyses indicated that bipolar disorder, relative to healthy, participants also displayed elevated left‐lateral OFC (BA 47) activity during reward anticipation (p < 0.05, corrected). Conclusions: Elevated ventral striatal and OFC activity during reward anticipation may represent a neural mechanism for predisposition to expansive mood and hypo/mania in response to reward‐relevant cues that characterizes bipolar disorder. Our findings contrast with research reporting blunted activity in the ventral striatum during reward processing in unipolar depressed individuals, relative to healthy controls. Examination of reward‐related neural activity in bipolar disorder is a promising research focus to facilitate identification of biological markers of the illness.